If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(10 + 2x) + -2(x + 4) = 14 (10 * -5 + 2x * -5) + -2(x + 4) = 14 (-50 + -10x) + -2(x + 4) = 14 Reorder the terms: -50 + -10x + -2(4 + x) = 14 -50 + -10x + (4 * -2 + x * -2) = 14 -50 + -10x + (-8 + -2x) = 14 Reorder the terms: -50 + -8 + -10x + -2x = 14 Combine like terms: -50 + -8 = -58 -58 + -10x + -2x = 14 Combine like terms: -10x + -2x = -12x -58 + -12x = 14 Solving -58 + -12x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '58' to each side of the equation. -58 + 58 + -12x = 14 + 58 Combine like terms: -58 + 58 = 0 0 + -12x = 14 + 58 -12x = 14 + 58 Combine like terms: 14 + 58 = 72 -12x = 72 Divide each side by '-12'. x = -6 Simplifying x = -6
| 9=8*-5+8 | | 2y/3-8=2y+3 | | -9(5-4x)-(3x+5)=49 | | 2(m+4)=6 | | -4(10-8y)=24 | | k/2-4=-7 | | 5(x+2)=4(x-6) | | 2x^(3/2)=250 | | 7x^8-7=0 | | 2(7-w)-4=0 | | -6=b/5-10 | | 2x^3/2=250 | | 2g-4=10h | | 3=-b-6 | | 9+x/4=5 | | 5x-4-2x+3=-7-3x+5+2x | | -160=2-9x | | -7x+3=-4 | | 6=1+5(y-2) | | 5x+8=4x-1 | | 5m-2(m-5)=-17 | | -8+6n=82 | | -2p^2q^3=0 | | 14-1/3x-2 | | 2x+2-2x-1=14 | | -6=a/14-7 | | 8x^3+72x^2+160x=0 | | 2x+3=27-44x | | X^6+10=10 | | -7n+4=-129 | | 2d+20=6d | | 2x+3=27-4x |